2019
DOI: 10.1177/0969733019884614
|View full text |Cite
|
Sign up to set email alerts
|

Student nurses’ views of right to food of older adults in care homes

Abstract: Background: Human rights are an important part of nursing practice. Although there is increasing recognition regarding the importance of including human rights education in nursing education, few studies have focused on nursing students’ perspectives and experiences in relation to human rights in nursing, especially regarding older nursing home residents’ right to food. Objective: To explore nursing students’ perspectives and experiences in relation to the right to food. Research design: The study followed a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 36 publications
(51 reference statements)
0
8
0
Order By: Relevance
“… 7 , 13 , 26 In the present study, the nursing students recognized and addressed several structural challenges: in particular, the lack of professional chefs to prepare food and meals – a task that was left to the nursing students or healthcare staff; the lack of individual choice during mealtimes; the fact that some residents had to isolate themselves in their rooms due to stressful mealtimes with the other residents and inadequate routines for nutritional screening and documentation. 37 , 38 …”
Section: Discussion: Lessons Learnedmentioning
confidence: 99%
See 4 more Smart Citations
“… 7 , 13 , 26 In the present study, the nursing students recognized and addressed several structural challenges: in particular, the lack of professional chefs to prepare food and meals – a task that was left to the nursing students or healthcare staff; the lack of individual choice during mealtimes; the fact that some residents had to isolate themselves in their rooms due to stressful mealtimes with the other residents and inadequate routines for nutritional screening and documentation. 37 , 38 …”
Section: Discussion: Lessons Learnedmentioning
confidence: 99%
“…In our study, we found that learning took place when students talked about and reflected upon their own experiences with other students and with their supervisors, but also in their interactions with the residents. 37 , 38 The emphasis on context and relationship is not new to HRE. For instance, Tibbits argues that human rights learning and accountability develop through participation and socialization.…”
Section: Discussion: Lessons Learnedmentioning
confidence: 99%
See 3 more Smart Citations